2015
DOI: 10.1177/1753944715589887
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of whole blood viscosity, its determinants and relationship with arterial blood pressure in the community: cross-sectional analysis from the Gutenberg Health Study

Abstract: Background: Blood viscosity has a role in modulating cardiovascular homeostasis; changes in this parameter have been associated with cardiovascular mortality and morbidity. However, it remains unclear whether these changes are (1) involved in the pathophysiology of disease, (2) an epiphenomenon, or (3) the expression of counterregulatory mechanisms. We report data on the normal values of blood viscosity and its association with cardiovascular risk factors, prevalent cardiovascular disease, and blood pressure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 27 publications
(35 reference statements)
2
13
0
Order By: Relevance
“…Premenopausal women had significantly lower hematocrit (45.8 ± 2.7% versus 40.0 ± 2.4%, p < 0.001) and higher erythrocyte deformability (erythrocyte rigidity index: 3.1 ± 0.1 versus 2.8 ± 0.1, p < 0.001) than agematched males, reflecting monthly physiologic bleeding and erythrocyte renewal [Kameneva et al 1999]. We agree with the findings reported by Gori and colleagues and believe that these findings were explained by the significantly larger difference of hematocrit between genders as opposed to differences in erythrocyte deformability [Gori et al 2015]. Also consistent with previous findings [Smith et al 1992], the authors reported significant positive associations between WBV and systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure (p < 0.0001 for all).…”
Section: Dear Editorsupporting
confidence: 91%
“…Premenopausal women had significantly lower hematocrit (45.8 ± 2.7% versus 40.0 ± 2.4%, p < 0.001) and higher erythrocyte deformability (erythrocyte rigidity index: 3.1 ± 0.1 versus 2.8 ± 0.1, p < 0.001) than agematched males, reflecting monthly physiologic bleeding and erythrocyte renewal [Kameneva et al 1999]. We agree with the findings reported by Gori and colleagues and believe that these findings were explained by the significantly larger difference of hematocrit between genders as opposed to differences in erythrocyte deformability [Gori et al 2015]. Also consistent with previous findings [Smith et al 1992], the authors reported significant positive associations between WBV and systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure (p < 0.0001 for all).…”
Section: Dear Editorsupporting
confidence: 91%
“…In summary, our data support those of Gori et al [ 5 ] but do not support either a U-shaped curve [ 31 ] or an inverse relationship between blood pressure and haematocrit [ 6 ].…”
Section: Discussionsupporting
confidence: 66%
“…Regardless of molecular size, plasma exchange removed substance with high protein‐binding affinity and provided more efficient removal of substance. However, it required plasma supplement and had risk of allergic reaction and transfusion‐related infection . DFPP removed substance selectively according to molecular weight without need for plasma supplement .…”
Section: Discussionmentioning
confidence: 99%
“…Total protein was measured by biuret reference method. WBV was estimated in centipoises (cP) at high shear rate (208 s −1 ) according to following equation as previous study: WBV = 0.12 × Hct + 0.17 × (total protein −2.07). The removal rate of triglyceride was calculated using the following formula: (pre‐apheresis TG - post‐apheresis TG)/pre‐apheresis TG.…”
Section: Methodsmentioning
confidence: 99%